Preharvest blue diode laser irradiation enhances betalain biosynthesis, antioxidant responses, and postharvest quality of red amaranth microgreens during storage - Supapvanich, Suriyan; Sripumimas, Sookmas; Li, Man; Kang, Chuankai; Puisoongnoen, Nichaphat; Konpha, Supawan; Yin, Xueren; Wen, Bo (My University, 2026)
In recent years, light-based technologies have attracted growing interest as a postharvest strategy for maintaining the quality of leafy vegetables and microgreens. This study investigated the effects of blue diode laser irradiation (450 nm, 3 h) on the postharvest quality, antioxidant system, and betalain biosynthesis of red amaranth (Amaranthus tricolor) microgreens during storage at 4 ± 1 °C for 9 d. Blue laser treatment effectively maintained visual quality and reduced weight loss compared with untreated samples. Treated microgreens exhibited significantly lower accumulation of hydrogen peroxide (H₂O₂), superoxide anion (O₂⁻), and lipoxygenase (LOX) activity during storage, indicating reduced oxidative stress and membrane lipid peroxidation. In addition, laser-treated samples maintained higher antioxidant capacity, including ferric reducing antioxidant power (FRAP) and DPPH radical scavenging activity, together with greater retention of total phenolics, flavonoids, vitamin C, and glutathione. Activities of antioxidant-related enzymes, including phenylalanine ammonia-lyase (PAL), superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX), were also significantly enhanced by laser irradiation. Furthermore, blue laser treatment effectively delayed chlorophyll degradation and increased betacyanin accumulation during storage. Gene expression analysis revealed significant upregulation of betalain biosynthesis-related genes, including AtrWRKY42–2, AtrCYP76AD1, AtrMYB72, AtrDODA1–1, and AtrB5-GT, particularly during the early storage period. Principal component analysis clearly separated laser-treated and control samples, confirming the positive association between laser irradiation, antioxidant defense, pigment retention, and overall quality maintenance. These findings demonstrate that short-term blue laser irradiation is a promising postharvest technology for enhancing antioxidant defense, regulating betalain biosynthesis, and extending the shelf life of red amaranth microgreens.
Keywords: Amaranthus tricolor; Antioxidants; Diode laser; Pigments; Postharvest quality